Analysis of formation damage caused by oil-based mud on berea sandstone using SEM - Ismail, Issham; Babu, Jagdeve (Penerbit UTM Press, 2004)
The objective of this experiment is to investigate the damage caused by oil-based mud on Berea sandstone using Scanning Electron Microscope (SEM). Laboratory experiments had been carried out using synthetic oil-based mud (Sarapar 147) at various differential pressures exerted on the core under dynamic conditions. The discussion of this research results were based on the damage ratio and visual observation of exposed samples using SEM. The damage ratios of the damage core samples were found to decrease when the differential pressures were increased. These results were confirmed with SEM images. The SEM images and damage ratios also revealed that when samples were positioned at an angle of 1800 (horizontal), they experienced higher particles plugging compared to samples positioned at an angle of 90o (vertical).